2005
DOI: 10.1002/bem.20118
|View full text |Cite
|
Sign up to set email alerts
|

Local heating of human skin by millimeter waves: Effect of blood flow

Abstract: We investigated the influence of blood perfusion on local heating of the forearm and middle finger skin following 42.25 GHz exposure with an open ended waveguide (WG) and with a YAV mm wave therapeutic device. Both sources had bell-shaped distributions of the incident power density (IPD) with peak intensities of 208 and 55 mW/cm(2), respectively. Blood perfusion was changed in two ways: by blood flow occlusion and by externally applied vasodilator (nonivamide/nicoboxil) cream to the skin. For thermal modeling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 47 publications
(74 reference statements)
3
66
0
Order By: Relevance
“…It is noted that water is also the major constituent of skeletal muscle, but because of the mentioned depth of the panniculus camosus muscle, it seems more likely that heat is transferred to blood and then to muscle. This idea is supported by the observations of Alekseev et al [2005] who noted that increased perfusion brought about a local decrease in temperature of irradiated human skin.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…It is noted that water is also the major constituent of skeletal muscle, but because of the mentioned depth of the panniculus camosus muscle, it seems more likely that heat is transferred to blood and then to muscle. This idea is supported by the observations of Alekseev et al [2005] who noted that increased perfusion brought about a local decrease in temperature of irradiated human skin.…”
Section: Discussionsupporting
confidence: 76%
“…In our study the panniculus carnosus muscle atrophied, despite being deeper than the suggested penetration depth of 94 GHz MMW, suggesting that the vascular system plays a large role in the distribution of heat during MMW exposure. Alekseev et al [2005] showed that tissue heating occurs in layers located deeper than the penetration depth of the MMW suggesting the influence of perfusion in heat distribution. Nelson et al [2000] showed that increased blood perfusion reduces the maximum surface temperature response to MMW exposure of a primate scalp model at 100 GHz.…”
Section: Status Of Effortmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of experimental studies, including our present experiments, have clarified the possible biological mechanisms of the treatment [Pakhomov et al, 1998b;Logani et al, 2002;Makar et al, 2003;Radzievsky et al, 2004a;Alekseev et al, 2005;Szabo et al, 2006]. Some clinical studies have demonstrated the effectiveness of MMWT under ''double-blind'' conditions [Korpan and Saradeth, 1995;Megdiatov et al, 1995;Radzievsky et al, 1999;Usichenko et al, 2003].…”
Section: Discussionmentioning
confidence: 78%